Obstacles to Sinhala Oral Communication among Deep-Sea Fishermen: A Phenomenological Study - Mohideen Bawa Nowzath; Singanayagam Umashankar; M.R Rishad Muhammed (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This phenomenological study explores the obstacles to effective Sinhala oral communication experienced by Tamil-speaking deep-sea fishermen in the Ampara District of Sri Lanka. Adopting a qualitative research design, data were collected from sixty fishermen through in-depth semi-structured interviews to capture their lived experiences of spoken communication in professional contexts. The data were analysed using Braun and Clarke’s (2006) thematic analysis framework. The study is theoretically grounded in Communication Accommodation Theory (Giles, 1973) and Cummins’ (1979) Linguistic Interdependence Hypothesis, providing insight into how linguistic adjustment, oral proficiency, and cross-linguistic transfer influence everyday communicative interactions. The findings reveal that limited Sinhala oral competence significantly hinders fishermen’s professional coordination, workplace safety, and collaborative engagement with Sinhalese fishermen and navy personnel. These obstacles stem not only from linguistic inadequacies in speaking and listening but also from broader sociocultural factors, including limited opportunities for sustained intergroup interaction and unequal access to spoken Sinhala learning resources. The study recommends the implementation of regionally responsive, hypermedia-based Sinhala oral communication programmes incorporating audio, visuals, animations, and interactive elements to support experiential language learning among junior fishermen. Such interventions are expected to enhance oral communicative competence, strengthen intergroup collaboration, and contribute to sustainable professional development within the deep-sea fishing community.